Balint-Ly Obvious: The Value of Balint Groups in Medical Education - Roshni Bahri; Ahmad Kamal Mohamad; Sian Davies; Azjad Elmubarak (BJPsych Open)
Aims: In collaboration with Birmingham Medical School, Birmingham Solihull Mental Health Foundation Trust (BSMHFT) Clinical Teaching Academy piloted a novel Balint Group (BG) scheme for 4th-year medical students during their psychiatry placement. To the best of our knowledge, this is the first time BGs have been accessible to 460 students in one year, and to every student attending psychiatry placement. Research shows that empathy declines in medical students as they progress through their career. However, BGs are known to improve student empathy and support the development of a clinical identity, yet no research has assessed whether through the process of Balint, students successfully gain skills in transference, emotional and cognitive learning, and case mirroring in group dynamics.